Importance of sports and recreational activities for people with disabilities - Slavković Sanela; Kibeček Sabina; Tamaš Daniela (College of Sports and Health, Belgrade, 2021)
The quality of life is a broad concept influenced by the physical health of an individual, their mental state, and the degree of independence, social relations and numerous variables from the environment. Sports and recreational activities can contribute to improving the quality of life of people with disabilities. The main goal of the survey is to determine the importance of sports and recreational activities for people with disabilities. The sample consists of 44 respondents, aged 18-63 (M=34.5) years. Respondents are engaged in various sports (competitive and recreational). Two questionnaires were used in the survey: the General Questionnaire (which contains questions on general socio-demographic data, as well as questions about training, motives for playing sports, the perception of the impact of sports on various aspects of an individual's life) and the Health Questionnaire (EQ-5D) which examines the health status of the general population and people with chronic diseases and/or disabilities. Based on the obtained results, it was found that people with disabilities perceive sport primarily as an opportunity for socializing and recreation, and half of the respondents view it as a profession. People with disabilities have motivation and desire to play sports and are aware of the positive outcomes that result from sports and recreational activities. The professional and scientific public could contribute to improving the conditions for them. It is necessary to open this topic and point out its importance so that a larger number of people with disabilities could have the opportunity to engage in a variety of sports and recreational activities.